Trends, Technology, and Implementation of Digital Counseling in a Human Mental Health - Agus Aan Jiwa Permana; Rukmi Sari Hartati; Made Sudarma; I Made Sukarsa (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2023)
This research discusses various trends, methods, and implementation of the art of digital-based counseling services. With increasing public awareness of mental health, since the womb, parents have thought about how to form good character and mental health for their children. Purpose of this study is to utilize digital counseling services to help early detection of depression and the resilience of children and adolescents in dealing with life's problems. This research collects articles according to the topic, then looks at cases handled, types of data, and methods used in both synchronous and asynchronous-based digital counseling. The next stage is research grouping based on research objects, data, methods, results, and deficiencies in research. The focus of the research is on cases of depression, and resilience, with machine learning methods. Digital counseling has been widely used for early detection in cases of depression, drug abuse, youth suicide, and alcohol addiction among adolescents